Sumienie jako własność i wyróżnik osoby w jej procesie rozwoju - Wrońska, Katarzyna (Horyzonty Wychowania, 2017)
The presented text is an attempt to understand the sense ofconscience through the description of its manifestations in thewhole dynamics of development, adolescence, upbringing, andalso going astray, regression and suppression throughout person’slife as well as in the entirety of his experiences. Thephenomenon of conscience revealing itself in the direct experienceas a „voice”, „talking” with warning or accusation because ofthe intended or already done evil turns out to be pain, complaint,suffering of the heart because of the damage or failure to dogood. When undertaken (heard) by a person, it can promptreflection and willingness to improve one’s life, since it creates,together with the whole sphere of cognitive experiences and will,moral awareness. The voice of conscience requires, as itsfoundation, cognitive acts of awareness and the knowledge ofgood and evil built in this manner, of moral obligations and one’s own attitude towards them, the ability to formulate judgements concerning one’s own actions and other people, as well as theability to translate general moral principles and use them in a particular situation. It also requires a general insight into values an axiological sensitivity.